Предмет: Алгебра,
автор: leratrifonova1
помогите пожалуйста решить
Ответы
Автор ответа:
0
x²+3^x+2=x²+9^x-3^x
x²+9^x-3^x-x²-3^x-2=0. 9^x-2*3^x-2=0 (3^x)²-2*3^x-2=0
пусть 3^x=t. t>0 t²-2t-2=0 D=4-4*1*-2=4+8=12
t1=(2+2√3)/2=1+√3
t2= 1-√3
1-√3 -посторонний корень
имеем 3^x=1+√3 x=log3 (1+√3)
как-то так
x²+9^x-3^x-x²-3^x-2=0. 9^x-2*3^x-2=0 (3^x)²-2*3^x-2=0
пусть 3^x=t. t>0 t²-2t-2=0 D=4-4*1*-2=4+8=12
t1=(2+2√3)/2=1+√3
t2= 1-√3
1-√3 -посторонний корень
имеем 3^x=1+√3 x=log3 (1+√3)
как-то так
Похожие вопросы
Предмет: Математика,
автор: jdndbxksoej
Предмет: Алгебра,
автор: licmanukanna22
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: Mika13
Предмет: Математика,
автор: 998116351